Congenital syphilis : a study at Provincial Hospital Uitenhage - Esselaar, Annette (Department of Paediatrics and Child Health, 2018)
Aims: 1. To establish the extent of Syphilis in Pregnancy and the association of syphilis with unbooked status and perinatal deaths. 2. To determine why the diagnosis was not made in forty cases of Early Congenital Syphilis. Objectives: 1. To establish the percentage of patients with syphilis at delivery and possible association between unbooked status and positive syphilis serology. 2. To determine the Perinatal Mortality Rate and establish what percentage of perinatal death s occurred in unbooked patients and in those with positive syphilis serology. 3. To establish booking status, place of delivery, whether treated or not, serological findings, signs and symptoms of infants with Early Congenital Syphilis. Study Design: 1. A descriptive, retrospective study of deliveries in the month of March 1994. 2. A descriptive, prospective study of perinatal deaths over six-month period January to Jun e 1995. 3. A descriptive, retrospective study of Early Congenital Syphilis patients over five-year period 1990 - 1994. Setting: Maternity and paediatric wards at Provincial Hospital Uitenhage, East Cape. Patients and Methods: 1. Records were studied of 154 maternity patients delivering in March 1994 in order to ascertain booking status and serology results. 2. Data on sixty-one perinatal deaths weighing over 500 grams was examined to establish maternal booking and serological status. 3. Folders of forty patients with Early Congenital Syphilis admitted to the paediatric ward were examined. Results: 1. Syphilis in Pregnancy: i) Prevalence of syphilis at delivery was 9% for patients with titres =/> 1 :8. ii) Unbooked patients totalled 47% of deliveries (73/154). iii) Fifteen percent of deliveries had no syphilis serology tests performed and were discharged without screening (23/154). iv) No significant association was found between unbooked status and positive serology (p=0.35). 2. Perinatal Deaths: i) In instances of a perinatal death, a significant association was found between unbooked status and positive RPR serology (p=0.017). ii) Perinatal death rate due to syphilis totalled 10.8/1000 deliveries. 3. Early Congenital Syphilis: i) Eighty-five percent of cases (34/40) delivered at PHU and were mismanaged by personnel. ii) Eighteen of the thirty-four mothers had attended antenatal clinic and were untreated or inadequately treated by the time of delivery (53%). vii iii) Sixteen of the mothers had been unbooked and were discharged without screening or treatment (47%). iv) Four booked patients had negative sousveillance during the antenatal period. Conclusion: Provincial Hospital Uitenhage serves a poor community. This is reflected in the high prevalence of syphilis at delivery and the high proportion of unbooked patients. Time-consuming and inefficient methods of sero-surveillance plus separate clinics and staff for antenatal and Sexually Transmitted Diseases compounded existing problems. The standard of care anticipated at a Level 2 Referral Hospital was not delivered by Health Workers, largely due to lack of in-service training and guidelines for the management of Syphilis in Pregnancy. Recommendations: 1. In-service staff training by the Perinatal Education Programme (PEP) and adoption of protocols of management. 2. Rapid ("same-day") availability of serology results and initiation of treatment at Antenatal Clinic. 3. RPR at booking visit and repeated at delivery in all patients. 4. Monthly evaluation by Perinatal Problem Identification Programme (PPIP) and Obstetric/Paediatric meeting to monitor implementation.